Adversity quotient of students during covid-19 outbreak - Asni Asni; Siti Salsa Nabilah; Nurul Fajri; Dini Chairunnisa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Adversity quotient is one of the intelligences possessed by a person in managing difficulties into a challenge that must be resolved to achieve certain goals. So that the adversity quotient must be owned by students to face various difficulties in completing lectures. However, during the Covid-19 pandemic, student activity became limited, both in following the learning process and guidance in completing final assignments in the form of a thesis, which was increasingly difficult. The purpose of this study was to determine the level of adversity quotient of students during the Covid-19 pandemic. This research method is descriptive quantitative. The sample in this study numbered 237 students and were selected using proportional random sampling technique. This study uses an adversity quotient scale with a reliability level of 0.924 in the very good category. The data analysis technique used the score range/categorization formula. The results showed 7.2% or 17 guidance and counseling students had low adversity quotient, 67.1% or 159 students had medium adversity quotient and 25.7% or 61 students had high adversity quotient. It can be concluded that students in general tend to have a moderate adversity quotient during the Covid-19 epidemic. These findings indicate it is necessary to conduct a college level counseling and guidance program to increase the adversity quotient of students.